Onething You Can't Do In Heaven - Cahill,Mark (Rockwall,Texas Biblical Discipleship Publishers, 2004)
Are you ready for eternity? If so, are you helping others get ready for that journey into eternity that each of us must take? As believers, we all know we should tell others about the Lord, but we often don't know how. This practical book will give you id
Keywords: Witness bearing (Christianity) Evangelistic work